“I did it without hesitation. Am I the bad guy?”: Online conversations in response to controversial in-game violence - Bowman, Nicholas David; Bowen, Daniel A; Mercado, Melissa C; Resignato, Lindsey Jean; de Villemor Chauveau, Philippe (New media & society, 2024)
Video game content has evolved over the last six decades, from a basic focus on challenge and competition to include more serious and introspective narratives capable of encouraging critical contemplation within gamers. The “No Russian” mission from Call of Duty: Modern Warfare 2 casts players as terrorists responsible for the murder of innocent bystanders, sparking debate around how players engage and react to wanton violence in modern video games. Through thematic analysis of 649 Reddit posts discussing the mission, 10 themes emerged representing complexity in player experiences. Those themes were grouped into categories representing (descending order), (1) rote gameplay experiences, (2) dark humor, (3) comparing the mission to other games and real-world events, and (4) self-reflective eudaimonic reactions to the mission. Although less common, the presence of eudaimonic media effects (in at least 15% of posts) holds promise for the use of video games as reflective spaces for violence prevention.